2016
DOI: 10.1073/pnas.1522419113
|View full text |Cite
|
Sign up to set email alerts
|

Integration of parallel mechanosensory and visual pathways resolved through sensory conflict

Abstract: The acquisition of information from parallel sensory pathways is a hallmark of coordinated movement in animals. Insect flight, for example, relies on both mechanosensory and visual pathways. Our challenge is to disentangle the relative contribution of each modality to the control of behavior. Toward this end, we show an experimental and analytical framework leveraging sensory conflict, a means for independently exciting and modeling separate sensory pathways within a multisensory behavior. As a model, we exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 22 publications
3
74
2
Order By: Relevance
“…Control theory provides a common framework to quantify and interpret the behaviour of the whole animal through perturbations to exogenous reference signals and measurements of corresponding behavioural responses (for reviews, see [13,14]). Closed-loop neuromechanical modelling has been used to investigate the feedback control of diverse biological systems and behaviours, including flight control in moths [15,16] and flies [17 -19], flower tracking in moths [20], postural balance in humans [21,22] and refuge-tracking in fish [8,23,24].…”
Section: Closed-loop Model Of Multisensory Controlmentioning
confidence: 99%
“…Control theory provides a common framework to quantify and interpret the behaviour of the whole animal through perturbations to exogenous reference signals and measurements of corresponding behavioural responses (for reviews, see [13,14]). Closed-loop neuromechanical modelling has been used to investigate the feedback control of diverse biological systems and behaviours, including flight control in moths [15,16] and flies [17 -19], flower tracking in moths [20], postural balance in humans [21,22] and refuge-tracking in fish [8,23,24].…”
Section: Closed-loop Model Of Multisensory Controlmentioning
confidence: 99%
“…A notable vertebrate example is the mottled sculpin Cottus bairdi, of which lake and river populations weigh the two modalities differentially (Coombs and Grossman, 2006). Likewise, the hawkmoth Manduca sexta relies on the integration of these same two modalities to stabilize its flight (Roth et al, 2016). The leech, with its comparatively much smaller nervous system, cannot match these other animals in sophistication of behavior, but it presents a rare opportunity to study sensory integration in a simple and accessible nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…In any case, it is clear that flight control is typically multimodal with mechanosensation working in tandem with vision and various methods are available that can disentangle the cues (e.g. [75,76]). A comprehensive recent study [77] has shown that generation of steering motor commands that are known to be the result of visual perception, is modulated (in opposing ways) by mechanosensory information from the wings and halteres.…”
Section: Flight Control From Wing Strain Sensingmentioning
confidence: 99%